Form and transformation of the shape of the «Kazakh yort» in a new architecture of Astana - Sariev N. Сариев Н. (Рroblems of engineering and professional education, 2023)
The article discusses the current aspects of the formation of modern architecture of Kazakhstan based on the use of characteristic elements and images of national architecture, as well as decorative and applied art on the example of the new building of the Schoolchildren’s Palace in Astana.